Prevalence of Burnout Among Healthcare Workers During the COVID-19 Pandemic: A Systematic Literature Review - Beebee Zeba Mahetaab Mubarak Jan; Sumera Bibi Keenoo (BJPsych Open, 2025)
Aims: Burnout among healthcare workers has been a significant issue exacerbated by the COVID-19 pandemic. This review aims to synthesise the existing literature on the prevalence, signs, symptoms, and risk factors of burnout among healthcare workers during the pandemic.